Resveratrol and Angiogenin-2 Combined With PEGDA/TCS Hydrogel for the Targeted Therapy of Hypoxic Bone Defects via Activation of the Autophagy Pathway - Dehui Fan; Hengping Liu; Zhenning Zhang; Meiyi Su; Zhixian Yuan; Ying Lin; Shuquan Yang; Wenqiang Li; Xintao Zhang (Frontiers Media S.A., 2021)
The guarantee of cell survival under hypoxic conditions and rapid vascularization is a key in tissue engineering strategies for treating bone defects. Our study aimed to establish the protective role of bone marrow mesenchymal stem cells (BMSCs) and human umbilical vein endothelial cells (HUVECs) in hypoxic conditions and realize rapid vascularization in bone defects. Resveratrol (Res), a non-flavonoid polyphenolic compound, and angiopoietin-2 (ANG2), a vascular activating factor, were applied to enhance BMSC and HUVEC survival, osteogenesis, and angiogenesis. The morphology, autophagy, viability, apoptosis, cycle, and osteogenic differentiation of BMSCs treated with Res were analyzed. The results indicated that Res could improve BMSC survival and differentiation via the autophagy pathway under hypoxic conditions. In addition, Res maintained HUVEC growth and proliferation in a hypoxic and ANG2 double-adverse environment via the autophagy pathway. To simulate a relatively hypoxic environment, small-aperture PEGDA/TCS hydrogels containing Res and ANG2 were prepared. BMSCs were cultured in the PEGDA/TCS scaffold and transplanted into a large tibial defect. CD31 immunofluorescence showed that the density and size of new blood vessels in the bone defect were significantly enhanced by ANG2 and Res at 8 weeks after surgery. H&E, Masson, and immunohistochemical staining results indicated that ANG2 combined with Res could promote new bone formation in defects. All these results suggested that Res combined with ANG2 may be a novel strategy for the targeted therapy of hypoxic bone defects with tissue engineering scaffolds.